2001
DOI: 10.1177/026553220101800406
|View full text |Cite
|
Sign up to set email alerts
|

Standardized assessment of the content knowledge of English language learners K-12: current trends and old dilemmas

Abstract: Within the context of accountability for US schools, standardized achievement tests are being used for increasingly 'high stakes' decisions for all students including those for whom English is a second language, even when their English language skills are not adequate for the task. This article discusses approaches to the standardized assessment of content knowledge for English language learners (ELLs), 1 including testing in the student's first language, the use of test accommodations, and measuring growth in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 5 publications
1
18
0
Order By: Relevance
“…For many EBs, assessment in their developing language often reflects more about where they are in their proficiency trajectory than what they know about content (Butler & Stevens, 2001). One of the most promising practices that reduces this kind of assessment bias involves the use of linguistic modifications (Abedi, 2002;Abedi, Hofstetter, Baker, & Lord, 2001), which are consistent with the kind of sheltered support teachers should provide in instruction.…”
Section: Assessment Although Scholars Have Long Called For the Impormentioning
confidence: 99%
“…For many EBs, assessment in their developing language often reflects more about where they are in their proficiency trajectory than what they know about content (Butler & Stevens, 2001). One of the most promising practices that reduces this kind of assessment bias involves the use of linguistic modifications (Abedi, 2002;Abedi, Hofstetter, Baker, & Lord, 2001), which are consistent with the kind of sheltered support teachers should provide in instruction.…”
Section: Assessment Although Scholars Have Long Called For the Impormentioning
confidence: 99%
“…Arcuino (2013) confirmed that older people did not perform well on computer-based international tests as a result of their low proficiency in computer skills. Butler and Stevens (2001) also emphasized the inequity of high stakes test for ELLs. This is because in some schools, students are made to mix with the high proficient students and it becomes the teacher's job to attend to the special need of the ELL.…”
Section: Issues Of Ells and High Stakes Tests Achievementmentioning
confidence: 99%
“…The term is a borrowed concept from the field of education of disability students used to characterize the extra attention to make up for their learning disabilities (Butler & Stevens, 2001). Abedi et al (2004) defined accommodation as the inclusion strategies used during assessments to provide equal opportunities for learners with low proficiency levels.…”
Section: Dealing With L2 Assessment Language Difficultiesmentioning
confidence: 99%
See 2 more Smart Citations